Wild bees (Hymenoptera: Apoidea) in an urban botanical garden in Buenos Aires, Argentina - Mazzeo, Nadia Melisa (2015)
We assessed bee diversity and abundance in a botanical garden in the city of Buenos Aires during two consecutive spring–summer periods. Every 15 days, we collected by hand-netting bee specimens seen foraging on flowers during five-minute censuses at every entomophilous herbaceous plant. A total of 66 bee species (Hymenoptera: Apoidea) were recorded. Richness and abundance of native, generalist, and above-ground nesting (cavities) species were higher than that of exotic, specialist, and below-ground (soil) nesting ones, respectively. Social bees were more abundant, while the richness of solitary species was higher than that of social bees. Cleptoparasitic species were represented by a high number of species, even though only a few individuals were captured. Our results suggest that the studied area is an important bee reservoir within the city.